2018
DOI: 10.5705/ss.202016.0185
|View full text |Cite
|
Sign up to set email alerts
|

A Further Study of Propensity Score Calibration in Missing Data Analysis

Abstract: Methods for propensity score (PS) calibration are commonly used in missing data analysis. Most of them are derived based on constrained optimizations where the form of calibration is dictated by the objective function being optimized and the calibration variables used in the constraints. Considerable efforts on pairing an appropriate objective function with the calibration constraints are usually needed to achieve certain efficiency and robustness properties for the final estimators. We consider an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For nonsurvival outcomes, Han and Wang 17 evaluated the efficiency of their multiply robust estimator when both the propensity score and the data distribution are correctly modeled, but a theoretical efficiency comparison to the IPW estimator is unclear if only a propensity score model is correct. Han 48 proposed estimators for which incorrect models can always help improve efficiency as long as the propensity score is correctly modeled, which thus are always more efficient than the IPW estimator. Future work will formally examine the efficiency of the proposed estimator which focuses on time‐to‐event outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For nonsurvival outcomes, Han and Wang 17 evaluated the efficiency of their multiply robust estimator when both the propensity score and the data distribution are correctly modeled, but a theoretical efficiency comparison to the IPW estimator is unclear if only a propensity score model is correct. Han 48 proposed estimators for which incorrect models can always help improve efficiency as long as the propensity score is correctly modeled, which thus are always more efficient than the IPW estimator. Future work will formally examine the efficiency of the proposed estimator which focuses on time‐to‐event outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Han (2014b)), the dependence is rather complex, which makes a general comparison of efficiency between estimators using different working models very difficult. But the derivations provide some guidance on how the empirical process theory is applied, and the results give formulations of the asymptotic variance, both of which are important for investigations of efficiency under some specific situations such as those which were considered in Han (2018) for mean regression.…”
Section: Scenarios (B) and (C)mentioning
confidence: 99%
“…In the recent literature, Han 33 discussed that modifying the propensity scores as inverse weights essentially agrees with Deville and Särndal 1 in survey literature and showed that directly optimizing an objective function under calibration constraints leads to improving efficiency and robustness 34,35 . Likewise, a number of AIPW estimators have been proposed to calibrate the propensity scores by paring estimating equations and augmentation terms so that they achieve certain efficiency as well as dealing with double robustness 13,36‐38 .…”
Section: Discussionmentioning
confidence: 89%